A mediated magic the Indian presence in modernism 1880-1930 - Ahuja, Naman P.; Belfrage, Louise (Axel and Margaret Ax:son Johnson Foundation for Public Benefit, 2019)
"Through the chapters of this volume important traces of Hindu and Buddhist thought in Western Modernism become clear: from art to music, dance, psychology, theatre and architecture. We find an intriguing interplay between the artistic, scientific, cultural and spiritual spheres-from both Asia and Europe-mediated by extraordinary personalities such as Anna Pavlova, Léon Bakst, Helena Blavatsky, Annie Besant, Wassily Kandinsky, Natalia Goncharova, Rabindranath Tagore, Ananda Coomaraswamy and C.G. Jung."--Preface (page 7)
Keywords: Geschichte 1880-1930; Kunst; Moderne; Rezeption; Künste; Indien; Europa; Avantgarde; Aufsatzsammlung